Habitat and resource use by waterfowl in the northern hemisphere in autumn and winter - Davis, J. Brian; Guillemain, Matthieu; Kaminski, Richard M.; Arzel, CÃ©line; Eadie, John M.; Rees, Eileen C. (Wildfowl, 2014)
A particular aim of avian ecologists, especially those studying waterfowl Anatidae, in theÂ 20th and early 21st centuries has been to elucidate how organisms use habitats andÂ intrinsic resources to survive, reproduce and ultimately affect fitness. For much of theÂ 20th century, research was mainly on studying species during the breeding season;Â however, by the 1970s, the focus had changed to understanding migratory waterfowlÂ throughout their annual cycle and range in Europe and North America. Autumn andÂ winter are considered the non-breeding seasons, but habitat and resource use throughÂ these seasons is crucial for completing spring migration and subsequent breeding. HereÂ we review the literature on autumnal and winter habitat use by Nearctic and PalearcticÂ waterfowl to determine characteristics of important landscapes and habitats for the birdsÂ during autumn migration and in winter. Selection of habitats and resources is discussedÂ (when literature permits) in relation to Johnsonâ€™s (1980) model of hierarchical habitatÂ selection. Habitat use by selected species or groups of waterfowl is also reviewed, andÂ important areas for future research into habitat ecology are identified. We suggest thatÂ the greatest lack of understanding of waterfowl habitat selection is an ongoing inabilityÂ to determine what habitats and intrinsic resources, at multiple scales, are truly availableÂ to birds, an essential metric in quantifying â€œselectionâ€ accurately. Other significantÂ challenges that impede gaining knowledge of waterfowl ecology in the northernÂ hemisphere are also described. Nonetheless, continued technological improvements andÂ engagement of diverse interdisciplinary professional expertise will further refineÂ understanding of waterfowl ecology and conservation at continental scales.